An approximate solution for flow between two disks rotating about distinct axes at different speeds - Ersoy, H. Volkan (HINDAWI LTD, 2007)
The flow of a linearly viscous fluid between two disks rotating about two distinct vertical axes is studied. An approximate analytical solution is obtained by taking into account the case of rotation with a small angular velocity difference. It is shown how the velocity components depend on the position, the Reynolds number, the eccentricity, the ratio of angular speeds of the disks, and the parameters satisfying the conditions u = 0 and v = 0 in midplane.
Keywords: NAVIER-STOKES EQUATION; ASYMMETRIC FLOW; HEAT-TRANSFER; FLUID; Engineering; Mathematics